Endosomal Type Iγ PIP 5-Kinase Controls EGF Receptor Lysosomal Sorting - Sun, Yue (2013)
Endosomal trafficking and degradation of epidermal growth factor receptor (EGFR) play an essential role in control of its signaling. Phosphatidylinositol-4,5-bisphosphate (PtdIns4,5P(2)) is an established regulator of endocytosis, whereas PtdIns3P modulates endosomal trafficking. However, here we demonstrate that type Igamma phosphatidylinositol phosphate 5-kinase i5 (PIPKIγi5), an enzyme that synthesizes PtdIns4,5P(2), controls endosome to lysosome sorting of EGFR. In this pathway, PIPKIγi5 interacts with sorting nexin 5 (SNX5), a protein that binds PtdIns4,5P(2) and other phosphoinositides. PIPKIγi5 and SNX5 localize to endosomes, and loss of either protein blocks EGFR sorting into intraluminal vesicles (ILVs) of the multivesicular body (MVB). Loss of ILV sorting greatly enhances and prolongs EGFR signaling. PIPKIγi5 and SNX5 prevent Hrs ubiquitination and this facilitates the Hrs association with EGFR that is required for ILV sorting. These findings reveal that PIPKIγi5 and SNX5 form a unique signaling nexus that controls EGFR endosomal sorting, degradation, and signaling.